Development of Front-End Web Applications Utilizing Single Page Application Framework and React.js Library - Jonathan, Ricky; Suprihadi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
In an era marked by rapid technological advancements, the impact of these developments is profoundly significant, particularly in the context of the ubiquity and indispensability of the internet. Motivated by this modern landscape, this study focuses on employing the Single Page Application (SPA) technique for the development of the Mbantu website. Central to this research is the utilization of the React.js library. The methodology encompasses several key phases: a comprehensive literature review, thorough analysis of the problem domain, design and prototyping, and the implementation of React.js for front-end development. The application of the SPA technique is observed to offer notable benefits for developers, including enhanced efficiency and time savings in the web development process. The findings presented in the Results and Discussion section demonstrate that the incorporation of React.js substantially contributes to the development of Mbantu's front-end architecture. Rigorous unit testing is performed on each component to ensure robustness and error minimization. The study concludes with suggestions for future research aimed at expanding the Mbantu web application's feature set to further improve user experience.